Improving local-level government accountability - a study of the government's accountability within the land use planning and development context in the Western Cape - Du Plessis, Johannes Petrus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Public Management and Planning))--University of Stellenbosch, 2010.